2024
DOI: 10.1186/s13063-024-07913-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and brain mechanism of multi-target transcranial alternating current stimulation (tACS) on motor learning in stroke patients: study protocol for a randomized controlled trial

Ming-Hui Lai,
Xiao-Ming Yu,
Yan Lu
et al.

Abstract: Background Transcranial alternating current stimulation (tACS) has proven to be an effective treatment for improving cognition, a crucial factor in motor learning. However, current studies are predominantly focused on the motor cortex, and the potential brain mechanisms responsible for the therapeutic effects are still unclear. Given the interconnected nature of motor learning within the brain network, we have proposed a novel approach known as multi-target tACS. This study aims to ascertain wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Currently, TMS has the potential to be applied to the diagnosis and treatment of types of neuronal diseases, such as depression [81][82][83], stroke [84,85], multiple sclerosis [86][87][88], and limb paralysis [89,90], without the disadvantages of electrical stimulation therapies. Eddy currents not only have been used in the development of new therapies, but also complement currently available ones.…”
Section: Medical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, TMS has the potential to be applied to the diagnosis and treatment of types of neuronal diseases, such as depression [81][82][83], stroke [84,85], multiple sclerosis [86][87][88], and limb paralysis [89,90], without the disadvantages of electrical stimulation therapies. Eddy currents not only have been used in the development of new therapies, but also complement currently available ones.…”
Section: Medical Applicationsmentioning
confidence: 99%
“…Sekino et al [78] observed that the current distributions in the brain using TMS depend on the characteristics of the coil used. The results showed that the neurons present in the cerebellum could be activated by inducing a magnetic field of 0.56 T. Currently, TMS has the potential to be applied to the diagnosis and treatment of types of neuronal diseases, such as depression [81][82][83], stroke [84,85], multiple sclerosis [86][87][88], and limb paralysis [89,90], without the disadvantages of electrical stimulation therapies. Eddy currents not only have been used in the development of new therapies, but also complement currently available ones.…”
Section: Medical Applicationsmentioning
confidence: 99%